Legal formalism: a comparison between Jori and Schauer - Pintore, Anna (2017)
This essay examines and juxtaposes Mario Jori’s and Frederick Schauer’s ideas on legal formalism. Although developed independently of each other, these ideas show remarkable similarities: both focus on the notion of norm or rule as a tool for clarifying the notion of legal formalism; both defend legal formalism from the criticisms routinely moved against it. The author maintains that Jori’s and Schauer’s theories may contribute to shed light on (and criticize) the controversial notion of defeasibility of legal rules; they may also contribute to scale down, from a legal-theoretical point of view, the novelties of contemporary constitutional orders; finally, it may help to better understand their working machinery.